A modalidade pela perspectiva sistêmico-funcional na construção da argumentação em um inteiro teor de acórdão - Bochett, Amanda Canterle (2018)
“Life cannot be evaluated based on the past, but through deeds, through continuity” (MINISTER CARMEN LUCIA). This statement shows how important freedom of speech is. The need to guarantee freedom of speech made its insertion possible in Brazilian law through the Federal Constitution (1988) and the Civil Code (2002). The right to freedom of speech emerged during the polemic of non-authorized biographies (2013 to 2015), which generated the full judgment text of the Direct Unconstitutionality Action (ADI) 4.815. Thus, the aim of this thesis is analyzing the dimension of legal discourse to elucidate the contribution of modality to the elaboration of argumentation and to the realization of sociosemiotic processes that constitute a full judgment text. For the discursive-semantic analysis, this study is theoretically based on Haberma’s (1997) Discourse Theory of Law, by exposing how processes that generate deliberation are built. It is also based on Toulmin’s (2006) approach in regards to the uses of argument and the configuration of sociosemiotic processes (MATTHIESSEN, 2015) in the development of the full judgment text. The grammatical description is based on Systemic Functional Linguistics (HALLIDAY; MATTHIESSEN, 2014) that, besides Register Cartography (MATTHIESSEN, 2015), adopts modality as a determinant of the different degrees of commitment of speakers in their discourse. The methodological procedures, which are qualitative and quantitative, allowed us to determine the relationship between legal discourse, argumentation, social activity, and register. As a result, there is the composition of the full judgment text in fourteen main social activities, which are constituted by three primary sociosemiotic processes, which are Expounding, Enabling and Exploring, being the latter the one that most occurs. Similarly, in regards to argumentation, various compositions of the use of arguments of both the reporting justice and institutions/authorities and ministers in each social activity were identified. Among the sociosemiotic processes, Expounding could be considered as having power and commitment through modality, by explaining and categorizing opinion; Enabling, although presenting a lower number of modality occurrences, meets the requirement of legitimation of legal, constitutional precepts, and Exploring uses modality as a way to argument and review past facts.